Genetic Relatedness, Emotional Closeness and Physical Aggression: A Comparison of Full and Half Sibling Experiences - Roxanne Khan; Gayle Brewer; John Archer (Europe's Journal of Psychology, 2020)
Two studies investigated whether perceived closeness of siblings, and aggression between siblings, were associated with genetic relatedness. In following Hamilton’s rule, we predicted that as the coefficient of relatedness between siblings increased, emotional closeness would also increase while conflict would decrease. Contrary to the predictions, we found no effect of genetic relatedness in Study 1 when we compared participants’ (n = 240) ratings of emotional closeness; participants also reported significantly higher levels of conflict with full siblings than with half siblings. In Study 2, participants (n = 214) also reported a higher frequency of physical aggression with full siblings than with half siblings. These findings were contrary to the prediction from Hamilton’s rule. We discuss them in relation to parental investment in biological and non-biological offspring.